The neurocognitive profile of post‐traumatic stress disorder (PTSD), major depressive disorder (MDD), and PTSD with comorbid MDD - Sheri‐Michelle Koopowitz (Brain and Behavior, 2021)
Abstract Objective Neurocognitive dysfunction has been associated with post‐traumatic stress disorder (PTSD) and major depressive disorder (MDD). However, although PTSD is often comorbid with MDD, there is little neurocognitive work to date on individuals who suffer from both PTSD and MDD. Here, we compared neurocognitive domains in individuals with PTSD, MDD, and comorbid PTSD and MDD with those of healthy controls. Methods Participants comprised of mothers enrolled in the Drakenstein Child Health Study, a study exploring child health determinants in the Drakenstein district, Western Cape. N = 175 mothers (between 18 and 50 years) were recruited and divided into 4 groups: PTSD, MDD, PTSD with MDD, and healthy controls. Participants were assessed using the computerized NIH Toolbox, and paper and pencil neurocognitive tests. Domains assessed included executive function, memory, attention, learning, and processing speed. Results Distinct patterns of neurocognitive dysfunction were observed in this sample. PTSD was associated with more intrusion errors and MDD was associated with delayed recall impairment, relative to healthy controls. PTSD with comorbid MDD was associated with processing speed impairments, relative to healthy controls, and monodiagnostic groups. No group differences were observed on measures of attention and executive function. Conclusion Distinct patterns of neurocognitive dysfunction were associated with diagnoses of MDD and PTSD. Greater anticipated dysfunction and impairment in comorbid PTSD and MDD was not observed, however. Further work is needed to replicate and extend these findings.